To investigate the effect of administrative/legal factors on organizational performance: A Study of Selected Medium Sized Manufacturing Enterprises in Nairobi, Kenya - Gichunge, Evangeline M.; Kiberia, Francis N.; Thoruwa, Thomas F.N. (IJRDO - Journal of Business Management, 2021)
Political factors define the legal, administrative and regulatory framework within which organizations operate. Political/legal variables are state oriented and at both national and local level can affect an organization’s activities on a day to day basis through its laws, policies and authority. It can thus affect an organization’s strategic decisions by creating opportunities and threats, which arise because the political environment can determine the structure of an industry through monopoly and restricted trade practices.This study investigated the effect of administrative/ legal factors on organizational performance. The research was conducted through a descriptive survey of MEs in Nairobi, Kenya. Eighty Medium Enterprises (MEs) were selected using simple random sampling from a population of 165 MEs in Nairobi. Primary data was collected using a semi-structured questionnaire. The respondents who were members of management team filled open and close ended questions. The data was analyzed statistically using the SPSS and R packages through tabulation, proportions and Z-statistics. The results show evidence that the level of organization performance is affected by administrative/legal factors. The higher the influence of administrative/legal factors the lower the performances. An enabling legal, administrative and regulatory environment is imperative for ME sector to play an effective role as an engine for economic growth, poverty eradication and employment creation.